Bismuth Interfacial Doping of Organic Small Molecules for High Performance n‐type Thermoelectric Materials. (5th August 2016) - Huang, Dazhen; Wang, Chao; Zou, Ye; Shen, Xingxing; Zang, Yaping; Shen, Hongguang; Gao, Xike; Yi, Yuanping; Xu, Wei; Di, Chong‐an; Zhu, Daoben
Abstract: Development of chemically doped high performance n‐type organic thermoelectric (TE) materials is of vital importance for flexible power generating applications. For the first time, bismuth (Bi) n‐type chemical doping of organic semiconductors is described, enabling high performance TE materials. The Bi interfacial doping of thiophene‐diketopyrrolopyrrole‐based quinoidal (TDPPQ) molecules endows the film with a balanced electrical conductivity of 3.3 S cm −1 and a Seebeck coefficient of 585 μV K −1 . The newly developed TE material possesses a maximum power factor of 113 μW m −1  K −2, which is at the forefront for organic small molecule‐based n‐type TE materials. These studies reveal that fine‐tuning of the heavy metal doping of organic semiconductors opens up a new strategy for exploring high performance organic TE materials.